Unknown Aspects of Self-Assembly of PbS Microscale Superstructures - Querejeta-Fernández, Ana (2012)
A lot of interesting and sophisticated examples of nanoparticle (NP) self-assembly (SA) are known. From both fundamental and technological standpoints this field requires advancements in three principle directions: a) understanding the mechanism and driving forces of three-dimensional (3D) SA with both nano- and micro-levels of organization; b) understanding of disassembly/deconstruction processes; and c) finding synthetic methods of assembly into continuous superstructures without insulating barriers. From this perspective, we investigated the formation of well-known star-like PbS superstructures and found a number of previously unknown or overlooked aspects that can advance the knowledge of NP self-assembly in these three directions. The primary one is that the formation of large seemingly monocrystalline PbS superstructures with multiple levels of octahedral symmetry can be explained only by SA of small octahedral NPs. We found five distinct periods in the formation PbS hyperbranched stars: 1) nucleation of early PbS NPs with an average diameter of 31 nm; 2) assembly into 100–500 nm octahedral mesocrystals; 3) assembly into 1000–2500 nm hyperbranched stars; 4) assembly and ionic recrystallization into six-arm rods accompanied by disappearance of fine nanoscale structure; 5) deconstruction into rods and cubooctahedral NPs. The switches in assembly patterns between the periods occur due to variable dominance of pattern–determining forces that include vander Waals and electrostatic (charge-charge, dipole-dipole, and polarization) interactions. The superstructure deconstruction is triggered by chemical changes in the deep eutectic solvent (DES) used as the media. PbS superstructures can be excellent models for fundamental studies of nanoscale organization and SA manufacturing of (opto)electronics and energy harvesting devices which require organization of PbS components at multiple scales.